Response of irradiated mice to live-virus (TC-83) immunization. - Spertzel, R O (1975)
Studies were conducted to determine the effects of sublethal, acute, total-body irradiation (600 R) on the immune response of mice to a replicating antigen. Irradiation was performed at varying times (0 to 21 days) prior to immunization with attenuated Venezuelan equine encephalomyelitis virus, TC-83. Development of protective immunity was studied by inoculating subgroups of irradiated mice with virulent Venezuelan equine encephalomyelitis virus on days 1 through 28 after immunization. Irradiation failed to affect the overt clinical response of mice inoculated with the attenuated strain, but antibody responses and the onset of protective immunity was delayed, particularly in mice irradiated 2 h to 3 days prior to vaccination. Immunity afforded by TC-83 developed more rapidly as the interval between irradiation and vaccination increased: when this interval was 14 or more days, the temporal course of immune response in irradiated mice was similar to that of nonirradiated vaccines. Persistence of TC-83 viremia was greatly prolonged in irradiated mice through the irradiation recovery period and probably provided the antigenic stimulus responsible for delayed development of effective immunity.